Successful Treatment of Rhino-Orbital Mucormycosis with Posaconazole and Hyperbaric Oxygen Therapy. (13th March 2013) - Almannai, Mohammed; Imran, Hamayun; Estrada, Benjamin; Siddiqui, Abdul Hafeez
<x xml:space="preserve">Abstract</x> Mucormycosis is a rare, but invasive infection caused by ubiquitous molds. Amphotericin B and surgery have been known to help improve the outcome. Sporadic case reports support the use of posaconazole in adults. We report a toddler with acute lymphoblastic leukemia who acquired rhino-orbital mucormycosis caused by Rhizopus species at the end of induction chemotherapy. She was successfully treated with multiple surgical debridements, amphotericin B, posaconazole and hyperbaric oxygen therapy. In conclusion, mucormycosis is a serious infection that requires aggressive surgical and medical therapy. To the best of our knowledge the use of posaconazole combined with hyperbaric oxygen therapy has not been reported in a toddler with leukemia and invasive Rhizopus sp. infection. This approach was found to be safe and effective in our patient.